Characterization of light chain c-terminal extension sequence variant in one bispecific antibody - Lin, Jun; Xie, Mengyu; Liu, Dan; Gao, Zhen; Zhao, Xiaoyan; Ma, Hongxia; Ding, Sheng; Li, Shu mei; Li, Song; Liu, Yanling; Zhou, Fang; Hu, Hao; et al. (Frontiers in Chemistry, 2022)
Protein modifications such as post-translational modifications (PTMs) and sequence variants (SVs) occur frequently during protein biosynthesis and have received great attention by biopharma industry and regulatory agencies. In this study, an aberrant peak near light chain (LC) was observed in the non-reduced capillary electrophoresis sodium dodecyl sulfate (nrCE-SDS) electrophoretogram during cell line development of one bispecific antibody (BsAb) product, and the detected mass was about 944 Da higher than LC. The corresponding peak was then enriched by denaturing sizing exclusion chromatography (SEC-HPLC) and further characterized by nrCE-SDS and peptide mapping analyses. De novo mass spectra/mass spectra (MS/MS) analysis revealed that the aberrant peak was LC related sequence variant, with the truncated C-terminal sequence “SFNR” (“GEC”deleted) linked with downstream SV40 promotor sequence “EAEAASASELFQ”. The unusual sequence was further confirmed by comparing with the direct synthetic peptide “SFNREAEAASASELFQ”. It was demonstrated by mRNA sequencing of the cell pool that the sequence variant was caused by aberrant splicing at the transcription step. The prepared product containing this extension variant maintained well-folded structure and good functional properties though the LC/Heavy chain (HC) inter-chain disulfide was not formed. Several control strategies to mitigate the risk of this LC related sequence variant were also proposed.